2017
DOI: 10.3389/fphar.2017.00795
|View full text |Cite
|
Sign up to set email alerts
|

Jiang Tang Xiao Ke Granule Play an Anti-diabetic Role in Diabetic Mice Pancreatic Tissue by Regulating the mRNAs and MicroRNAs Associated with PI3K-Akt Signaling Pathway

Abstract: Purpose: To investigate the effect of JTXK granule on the expression pattern of miRNA in pancreatic tissue of KKAy diabetic mice, and to explore the molecular mechanism and pathways of JTXK granule in anti-diabetic effect.Methods: We used high fat diet (HFD) to induce the KKAy diabetic mice and screened the differentially expressed miRNAs (DEMs) between JTXK-treated group (n = 6) and the diabetic group (n = 6) using MicroRNA (miRNA) Microarray. C57BL/6J mice were given a normal diet as the control group (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The batch number was 20140518. Fingerprint of this granule that illustrated the main ingredients were shown in Figure 1 and in accordance with our previous study (Mo et al, 2017). Finally, the granules were stored in −4 • C refrigerator and prepared suspension of corresponding concentration with distilled water before use.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The batch number was 20140518. Fingerprint of this granule that illustrated the main ingredients were shown in Figure 1 and in accordance with our previous study (Mo et al, 2017). Finally, the granules were stored in −4 • C refrigerator and prepared suspension of corresponding concentration with distilled water before use.…”
Section: Introductionsupporting
confidence: 80%
“…It has been found that Chinese medicine formula play a major role in the treatment of diabetes through multiple targets with various mechanisms (Zhijun et al, 2013) and so on. Our previous data have shown that JTXK Granule plays the anti-diabetic role by regulating glycolipid metabolism, resisting oxidative stress, and also protecting islet cells, which act through regulating phosphatidylinositol 3kinase (PI3K)/protein kinase B (AKT)-related microRNAs and mRNAs expressions in pancreatic tissues (Zhao et al, 2014;Mo et al, 2017;Yu et al, 2017). Another study also suggested that JTXK granule can regulate glycolipid metabolism in the liver tissue of diabetic mice (Yi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The 18 nucleosides in 5′ are identical to all family and constitute e form; the 3′ end of b is “GCAA,” of c “GU” and of d “A.” This miRNA does not harbor hexanucleotide element putatively facilitating addressing to nucleus ( 43 ). In addition, miR-320-5p has been reported only in diabetic mouse pancreatic tissue ( 40 ), no report in human. In rat, miR-320-3p is involved in embryo implantation ( 44 ) and in mouse is targeting heat-shock protein-20 (also hspb6) in cardiac ischemia/reperfusion injury ( 45 ) .…”
Section: Detection Of Mirna In Exosomes Associated With Type-2 Diabetmentioning
confidence: 99%
“…We identified strongly upregulated miR-320a in high GIP versus low GIP subjects. Transcriptomic data from mice pancreatic tissue point to miR-320 as the negative regulator of the mRNA associated with PI3K-Akt pathway, and hence disturbed nutrient metabolism and diabetes [78]. Recently, it has been documented that miR-320 inhibits SIRT1 expression via targeting the 3 UTR region of FoxM1 [79].…”
Section: Discussionmentioning
confidence: 99%